Range of Neurological Signs in Cynomolgus Monkeys After Intrathecal Bolus Administration of Antisense Oligonucleotides. (November 2020) - Korte, Sven; Runge, Frank; Wozniak, Magdalena M.; Ludwig, Florian T.; Smieja, Daniela; Korytko, Peter; Mecklenburg, Lars
Intrathecal (IT) dosing (ie, injection into the subarachnoidal space at the lumbar region) is a common route of administration in cynomolgus monkey preclinical safety studies conducted for antisense oligonucleotides (ASO) that target central nervous system diseases. Herein we report on neurological signs that have been observed in 28 IT studies conducted in 1, 016 cynomolgus monkeys. Neurological signs were classified into 5 groups: (1) A nonadverse transient absence of lower spinal reflexes. This observation occurred at low incidence in nontreated animals and in those that were injected artificial cerebrospinal fluid. The incidence increased in animals that were injected an ASO. Reflexes were present again at 24 hours or 48 hours after dosing. The incidence appeared to increase with dose. (2) Test-article-related adverse muscle tremor or muscle spasticity occurring during the injection procedure or immediately thereafter. In one-third of animals this finding responded to treatment with diazepam, in two-third it required euthanasia. (3) Neurological findings occurring between 30 minutes and 4 hours after dosing were characterized by any combination of ataxia, paresis, nystagmus, urinary incontinence, or muscle tremor. Those conditions either spontaneously resolved or they slowly worsened, eventually resulting in a poor general condition. (4) Neurological findings due to spinal cord injury were characterized by rapidly progressing paralysis of hind limbs. Magnetic resonance imaging revealed a focal hyperintense lesion, indicative of spinal cord necrosis. (5) Test-article-related adverse hind limb paresis or paralysis that occurred between 2 and 18 days after dosing. Those findings were rare and resulted in a poor general condition requiring euthanasia.